2003
DOI: 10.3748/wjg.v9.i12.2782
|View full text |Cite
|
Sign up to set email alerts
|

Changes of biological functions of dipeptide transporter (PepT1) and hormonal regulation in severe scald rats

Abstract: AIM:To determine the regulatory effects of recombinant human growth hormone (rhGH) on dipeptide transport (PepT1) in normal and severe scald rats. METHODS:Male Sprague-Dawley rats with 30 % total body surface area (TBSA)IIIdegree scald were employed as the model. In this study rhGH was used at the dose of 2 IU.kg

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…[16], chronic bowel diseases [17,18], 5-fluorouracilinduced intestinal damage [19], and malnourished condition [20,21]. Some hormones can metabolically regulated the expression of intestinal dipeptide transporter [8,33,34]. For example, insulin could increase the membrane population of PepT1 by increasing its translocation from a preformed cytoplasmic pool [35].…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…[16], chronic bowel diseases [17,18], 5-fluorouracilinduced intestinal damage [19], and malnourished condition [20,21]. Some hormones can metabolically regulated the expression of intestinal dipeptide transporter [8,33,34]. For example, insulin could increase the membrane population of PepT1 by increasing its translocation from a preformed cytoplasmic pool [35].…”
Section: Figmentioning
confidence: 99%
“…This raises questions as to the absorptive function of intestinal epithelial cell under these critical conditions. However, few studies in the literature were found to investigate the changes of absorptive function after trauma [8]. Small intestine is the major site of dietary protein absorption.…”
Section: Introductionmentioning
confidence: 99%
“…The level of the hPepT1 transporter is influenced by hormonal regulation (Adibi, 2003; Sun et al., 2003; Thamotharan et al., 1999), diet (Erickson et al., 1995; Shiraga et al., 1999), and disease (Sundaram et al., 2005; Ziegler et al., 2002). Three mechanisms have been proposed for regulation of hPepT1 expression.…”
Section: Discussionmentioning
confidence: 99%